THE INFLUENCE OF ACADEMIC SUPERVISION, TEACHER PROFESSIONAL COMPETENCE, AND SCHOOL LEADERSHIP ON PRIMARY SCHOOL MANAGEMENT QUALITY - Alma Wiyarti; Supandi Supandi; Nurkolis Nurkolis (JMIE (Journal of Madrasah Ibtidaiyah Education), 2026)
This research explores a comprehensive model of Primary School Management Quality by analyzing the contributions of academic supervision, teachers' professional competence, and school leadership. Using a quantitative approach, data were gathered from 145 primary school teachers in Kedungjati chosen through purposive sampling. A structured questionnaire was used to collect data from participants. The instrument developed from established literature, included several constructs such as academic supervision, teacher professional competence, school leadership, and school management quality. Each construct was evaluated using multiple indicators adapted from previous studies and measured on a five-point Likert scale from strongly disagree to strongly agree. Before testing the hypotheses, the instrument's validity and reliability were assessed. The findings indicated that all items were valid and reliable, with Cronbach’s alpha values surpassing 0.80 for each construct. Additionally, classical assumption tests, including normality, multicollinearity, heteroscedasticity, and linearity, confirmed that the data were suitable for multiple linear regression analysis. However, school leadership did not exhibit a statistically significant direct effect at the 95% confidence level. Nonetheless, the simultaneous test revealed that the three variables collectively enhance the model's explanatory power, with an R² value of 0.792. These results imply that Primary School Management Quality is mainly influenced by instructional supervision and teacher competence, while school leadership might function through indirect or contextual pathways. This study offering empirical evidence on the integrated yet distinct roles of essential school-level factors and provides practical insights for supervisors, school principals, and education policymakers.